Cost-benefit analysis : (Pearson/Prentice Hall, 2014)
For courses in Cost-Benefit Analysis, taught in Economics Departments, Public Policy Departments, and Public Administration Departments. Also ideal forpracticing policy analysts andpublic managers.This authoritative, market leading book is distinct for it's consistent application of a nine-step framework for conducting or interpreting a cost-benefit analysis.